Helping the Students to Navigate the Cultures of Others through Literature: The Teaching Practice to the Students of English Study Program in UIN SATU - Dwi Ima Herminingsih; Latifatul Isro’iyah (ELITE Association Indonesia, 2023)
The existence of hundreds of countries with billions of people absolutely has emerged the diversity of the culture in the world. Due to this fact, understanding the culture of different people will contribute some benefits to the students linguistically and culturally. The good comprehension of multicultural can make them be more aware of culture and be tolerant toward people whose backgrounds, perspectives and behave in the ways which are not the same. Having sufficient knowledge of diverse culture they can perform fine interpersonal communication to others better. Nonfiction literatures, science books as well as historical books are not the only media to gain the education of multicultural. Appreciating Fiction is another tool to nurture open-minded in the term of accepting of diversity of culture. The paper shares descriptively the teaching evidences how the students of University are driven to comprehend the culture of people in different areas of the world delivered by means of studying the literary works. This paper presents how the literary class run to equip the students with lesson of multicultural understanding. Firstly what are labelled as literature, specifically multicultural literature? Secondly how are the cultures told by the author? Thirdly why is it important to read literature? Fourthly, how multicultural literacy helps improving students’ performance in daily life? The presentation of the four topics are expected to bridge the students open their minds to accept the presence of culture of others that may be quite different from their own. In addition, they also can take something good or positive of the cultures shaped by people of other places. The new gained insights of life experiences, religion, and customs of other people become their modalities to build the unity within the diversity. Being not closed mind, they can appreciate or respect other, then they make their interpersonal relation or friendship with different ethnic, race and so on. Keywords: culture, literature, English, practice